Applying DNA rolling circle amplification in fluorescence imaging of cell surface glycans labeled by a metabolic method - Xiaoru Zhang; Ruijuan Li; Yuanyuan Chen; Shusheng Zhang; Wenshuang Wang; Fuchuan Li (2016)
We report herein imaging cell surface glycosylation by using click chemistry and DNA rolling circle amplification (RCA) to improve detection sensitivity..